Organisational impact: critical issues facing information technology management at a financial institution in South Africa - Beukes, Andre Charl (My University, 2016)
The aim of this research is to determine and analyse the 1110st important critical issues facing Information Technology (IT) Management at a major financial institution in South Africa, namely. First National Bank of Southern Africa Limited (FNB). Much has previously been written and researched on this subject. However, the information and findings has been based largely on international issues and trends. What is of particular relevance and IS emphasised in this research, are facton. influencing the local IT industry trends and critical issues in South Africa. Not only nrc we faced with the traditionally accepted industry-wide challenges, but there are certain issues and market conditions that could be considered unique to the local IT industry. Conclusions derived Iron' this research will provide factual data detailing what is currently considered as the 1110stimpcrtant critical issues at this particulnr financial institution. These will be ranked in order of importance as rated by a respondent group. The information analysed was obtained by means of questionnaires and interviews with a group of IT professionals from FNB. Although this qualitative information was obtained from one particular institution. the findings arc considered as having relevance and benefit to all participants in the local IT industry.
A research report submitted to the Faculty of Commerce, Unlvcrslty of the Witwatersrand, Johannesburg, ill partial fulfilment of the requirements for the degree of Mastel' of Commerce
Keywords: Banks and banking--South Africa--Data processing; Information technology--South Africa--Management